2018
DOI: 10.1101/444349
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High resolution atlas of the venous brain vasculature from 7 T quantitative susceptibility maps

Abstract: The vascular organization of the human brain can determine neurological and neurophysiological functions, yet thus far it has not been comprehensively mapped. Aging and diseases such as dementia are known to be associated with changes to the vasculature and normative data could help detect these vascular changes in neuroimaging studies. Furthermore, given the well-known impact of venous vessels on the blood oxygen level dependent (BOLD) signal, information about the common location of veins could help detect b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…SLFOs related to changes in heart rate and breathing patterns were found to affect mostly sensory regions including the visual and somatosensory cortices (particularly of the face) ( Figure 1A ), which correspond to regions with a high density of veins ( Bernier et al, 2018 ; Huck et al, 2019 ). The spatial pattern of SLFOs is very similar to statistical maps reported in prior works, which have highlighted brain regions highly correlated with the global signal ( Billings and Keilholz, 2018 ; Glasser et al, 2016 ; Li et al, 2019a ; Power et al, 2017 ; Tong et al, 2013 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…SLFOs related to changes in heart rate and breathing patterns were found to affect mostly sensory regions including the visual and somatosensory cortices (particularly of the face) ( Figure 1A ), which correspond to regions with a high density of veins ( Bernier et al, 2018 ; Huck et al, 2019 ). The spatial pattern of SLFOs is very similar to statistical maps reported in prior works, which have highlighted brain regions highly correlated with the global signal ( Billings and Keilholz, 2018 ; Glasser et al, 2016 ; Li et al, 2019a ; Power et al, 2017 ; Tong et al, 2013 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have developed digital atlases of the brain vasculature including either the arteries (Dunas et al, 2017) or the veins (Ward et al, 2018). Others have developed such digital atlases including both the arteries and the veins with (Bernier et al, 2018;Huck et al, 2018) or without (Passat et al, 2005;Viviani, 2016) separate labelling for these two vessel types. Future work could explore the use of these probabilistic digital atlases of the cerebral vasculature in patients with a vascular malformation.…”
Section: Discussionmentioning
confidence: 99%
“…However, this effect is not seen in our plots, which means that merely removing voxels inside veins or close to veins will not result in an elimination of their effect on the signal (fluctuation), especially at the used spatial resolution. Previous work also showed that the effects of the large veins (≥ 0.3 mm in diameter) can induce perturbations, which are perceptible even 6.7 mm away from the vein (Huck et al, 2023). Much smaller veins are probably not detectable with our method (Bause et al, 2020;Bollmann et al, 2022).…”
Section: Influence Of Large Veinsmentioning
confidence: 62%